Morphological characteristics of top soiling in the reclamation areas of post-coal mining at Kutai Kartanegara and Kutai Timur Regencies - Mulyadi Mulyadi; Makhrawie Makhrawie (Journal of Degraded and Mining Lands Management, 2023)
This study aimed to obtain information about the impact of different morphological characteristics and genesis at some reclamation sites after coal-mining activities. Two coal sites were chosen as study areas, i.e. the Separi site, which is located in Kutai Kartanegara regency and the Bengalon site, located in Kutai Timur Regency. A descriptive research method was used to identify the morphological characteristics of reclamation sites at different times (chronosequence). The results showed that in-situ weathering, indicated by soil leaching caused by rainwater infiltration, led to the formation of the Ah horizon more than two years after the reclamation activity. The process of material removal and disposal (cutting, filling, transporting and levelling) from coal mining operations tends to accelerate the decomposition of parent soil material and promote the formation of pre-cambic horizons. The soils used (horizon A, B, and C) for the topsoil of the reclamation site were initially Typic Hapludults and Typic Dystropepts, although Typic Tropaquents and sandy parent materials were also used. Due to the impermeable layers of overburdening where water channels in the soil profile and deeper layers have not yet formed as human-made soil and landscape (artificial) cause rainwater to fail to infiltrate deeper layers so that with less heavy rain, the groundwater level will rise to the surface and the land will become waterlogged/flooded.